Pengembangan Bahan Ajar Berbasis Kearifan Lokal Bojonegoro Unit III Pendidikan Pancasila Peserta Didik Kelas V di SDN Padangan III Bojonegoro - Dela Aulia Rindi Chikita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2024)
The use of teaching materials can influence the ongoing learning process, with the existence of teaching materials, educators will be helped in conveying messages contained in the learning materials and students will better understand what is conveyed in the material. Teaching materials developed according to the needs of students can be used to develop the application of values and morals. This development research uses the ADDIE model, which is a systematic methodology in instructional design. This model includes five different phases: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The results of the development of teaching materials based on local wisdom of Bojonegoro are said to be valid, effective and practical and can be used in learning. The validation results that have been assessed by the validator obtained a score of 92.4% which is categorized as very feasible. The effectiveness of teaching materials obtained a score of 88% and can be categorized as very effective. The practicality of teaching materials obtained a score of 79% and is included in the effective category. The practicality of teaching materials was obtained through student response questionnaires. Overall, it can be concluded that the teaching materials developed are effective and feasible to use during learning.
Reuploud file repositori 22228 Apr 2026_Firli_tata
Keywords: Local Wisdom; Pancasila Education; Teaching Materials